2009
DOI: 10.1186/1743-8977-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Expert elicitation on ultrafine particles: likelihood of health effects and causal pathways

Abstract: The overall medium to high likelihood rating of causality of health effects of UFP exposure and the high likelihood rating of at least one of the proposed causal mechanisms explaining associations between UFP and cardiac events, stresses the importance of considering UFP in future health impact assessments of (transport-related) air pollution, and the need for further research on UFP exposure and health effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 56 publications
2
127
0
Order By: Relevance
“…A European expert panel concluded that a reduction in UFP concentration by 10 000 particles cm −3 would lead to a decrease in all-cause mortality by 0.1-2.1 %, with the largest cause of uncertainty being the lack of long-term studies ). The experts defined as medium high the likelihood of a causal relationship of all-cause mortality and hospitalization data with short-term UFP exposure, while the link with long-term exposure was defined as medium (Knol et al, 2009). Mortality and cardiovascular morbidity data showed that UFP concentration is linked to delayed effects (Frostier et al, 2007;Stölzel et al, 2007;Wichman et al, 2000).…”
Section: Particulate Matter and Healthmentioning
confidence: 99%
“…A European expert panel concluded that a reduction in UFP concentration by 10 000 particles cm −3 would lead to a decrease in all-cause mortality by 0.1-2.1 %, with the largest cause of uncertainty being the lack of long-term studies ). The experts defined as medium high the likelihood of a causal relationship of all-cause mortality and hospitalization data with short-term UFP exposure, while the link with long-term exposure was defined as medium (Knol et al, 2009). Mortality and cardiovascular morbidity data showed that UFP concentration is linked to delayed effects (Frostier et al, 2007;Stölzel et al, 2007;Wichman et al, 2000).…”
Section: Particulate Matter and Healthmentioning
confidence: 99%
“…Based on epidemiological studies, there is still limited evidence on the effects on health of ultrafine particles , although the potential for such effects was considered to be large in a recent synthesis of opinions of experts (Knol et al, 2009).…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Healthbased guidelines for short-term formaldehyde exposure span a range of values (Salthammer et al, 2010). An expert elicitation review of the available literature rated the likelihood of increased short-term UFP exposure causing health effects as medium to high (Knol et al, 2009). Another review noted the substantial experimental evidence and plausible mechanisms for respiratory and cardiovascular effects of UFP intake, but deemed the evidence as "not sufficiently strong to conclude that short-term exposures to UFPs have effects that are dramatically different from those of larger particles" (HEI Review Panel on Ultrafine Particles, 2013).…”
Section: Introductionmentioning
confidence: 99%